Ghosts - Telgemeier, Raina (New York : Graphix, an imprint of Scholastic, 2016)
Catrina and her family have moved to the coast of Northern California for the sake of her little sister, Maya, who has cystic fibrosis--and Cat is even less happy about the move when she is told that her new town is inhabited by ghosts, and Maya sets her heart on meeting one.
Booklist starred
Pub Weekly
School Library Journal starred
Booklist starred, June 2016
Bulletin (Center for Children's books), July 2016
Horn Book, September 2016
Keywords: Cystic fibrosis -- Comic books, strips, etc -- Juvenile fiction; Families -- California, Northern -- Comic books, strips, etc -- Juvenile fiction; Ghosts -- Comic books, strips, etc -- Juvenile fiction; Moving, Household -- Comic books, strips, etc -- Juvenile fiction; Sisters -- Comic books, strips, etc -- Juvenile fiction; Cystic fibrosis -- Fiction; Family life -- California, Northern -- Fiction; Ghosts -- Fiction; Moving, Household -- Fiction; Sisters -- Fiction; Cystic fibrosis -- Comic books, strips, etc -- Fiction; Family life -- Northern California -- Comic books, strips, etc -- Fiction; Ghosts -- Comic books, strips, etc -- Fiction; Moving -- Comic books, strips, etc -- Fiction; Sisters -- Comic books, strips, etc -- Fiction; California, Northern -- Comic books, strips, etc -- Juvenile fiction; California, Northern -- Fiction; Northern California -- Comic books, strips, etc -- Fiction; Graphic novels; Paranormal comics